2017
DOI: 10.18632/oncotarget.17330
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial changes of cells positive for stem-like markers in different compartments and stages of human colorectal adenoma-carcinoma sequence

Abstract: Considerable evidence supports the idea that stem-like cells may play an essential role during the development of colorectal cancer (CRC). To accomplish this aim, we use immunohistochemistry (IHC) and double IHC with different potential stem-like markers, anti-musashi (Msi), anti-CD133, anti- LGR5 and anti-ALDH1 to examine the presentation of stem-like cells in different compartments including adenoma/CRC epithelium, transitional crypts and tumor stroma in colorectal adenoma and CRC. The results showed that ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…These findings were confirmed in another recent study [ 67 ]; in addition, in this study, it was observed that in serrated lesions other stem cell markers, such as EPHB2 and OLFM4, were distributed in a diffuse manner [ 67 ]. In addition to LGR5 + cells, the adenomatous epithelium also displayed an increased proportion of ALDH1-positive cells [ 68 ]. While in the normal colon positive cells, stem-like markers were shown in the base of normal crypts, in the adenomatous epithelium, the cells positive for stem-like markers were expressed as a patchy destruction on the surface of adenomatous crypts [ 68 ].…”
Section: Colorectal Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were confirmed in another recent study [ 67 ]; in addition, in this study, it was observed that in serrated lesions other stem cell markers, such as EPHB2 and OLFM4, were distributed in a diffuse manner [ 67 ]. In addition to LGR5 + cells, the adenomatous epithelium also displayed an increased proportion of ALDH1-positive cells [ 68 ]. While in the normal colon positive cells, stem-like markers were shown in the base of normal crypts, in the adenomatous epithelium, the cells positive for stem-like markers were expressed as a patchy destruction on the surface of adenomatous crypts [ 68 ].…”
Section: Colorectal Carcinogenesismentioning
confidence: 99%
“…In addition to LGR5 + cells, the adenomatous epithelium also displayed an increased proportion of ALDH1-positive cells [ 68 ]. While in the normal colon positive cells, stem-like markers were shown in the base of normal crypts, in the adenomatous epithelium, the cells positive for stem-like markers were expressed as a patchy destruction on the surface of adenomatous crypts [ 68 ].…”
Section: Colorectal Carcinogenesismentioning
confidence: 99%
“…Colorectal cancer (CRC) is one of the leading causes of high cancer-associated mortality worldwide. According to the colorectal adenoma-carcinoma sequence theory, most CRCs develop from pre-existing adenomatous lesions through a multistep process with the accumulation of genetic, molecular and histological changes (1, 2). This process is significantly influenced by host immunity (35).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously used a various set of cell markers, such as Musashi, CD133, LGR5 and ALDH1, as biomarkers to examine the presentation of SCs in different compartments of adenomas ( 17 ). We found that populations of SCs labeled by diverse markers were increased in the adenoma tissues.…”
Section: Pcscs/cscs In the Adenoma And Crc Tissuesmentioning
confidence: 99%
“…In addition, a spatial change in SCs in the adenoma was observed: SCs expanded from the base to the middle part of the transitional crypt and final finally reached the surface of the adenoma, reflecting a changed track pathway of SCs during the development of adenomas. Further analysis revealed that increased populations of LGR5 and aldehyde dehydrogenase 1 (ALDH1) labeled SCs in the adenoma were associated with the degree of dysplasia, suggesting the involvement of SCs in the establishment of adenomas ( 17 ).…”
Section: Pcscs/cscs In the Adenoma And Crc Tissuesmentioning
confidence: 99%